548 Implementation challenges in child-drowning prevention project in rural Bangladesh. (20th November 2022) - Bhuiyan, Md Al Amin; Ashraf, Lamisa; Agrawal, Priyanka; Alonge, Olakunle; Talab, Abu; Alam, Zobaer; Li, Qingfeng; Bachani, Abdulgafoor M; Fazlur Rahman, AKM; Rahman, Aminur
Abstract : Background: Globally, drowning is the leading cause of death, particularly in LMICs like Bangladesh, and has the highest rate among 1–4-year-old children. 'Saving of Lives from Drowning (SoLiD) in Bangladesh' has been rolled out with two interventions: Anchal (a community crèche) and Playpens with community education to save under-5 children from drowning in Bangladesh. So many challenges were found during the implementation. The study objective is to describe the implementation challenges of SoLiD in rural Bangladesh. Methodology: A descriptive study of the SoLiD implementation process in CIPRB field areas is described. Group work among different levels of project staff and periodic project reports were analysed to describe the challenges. Results: During SoLiD, 1600 Anchals were developed to supervise 20–25 children aged 1–5 years during the most vulnerable time of drowning, 9 am–1 pm. Dropout of trained caregivers and lack of qualified caregivers were major challenges, as they were interested in engaging themselves in full-time jobs rather than part-time volunteering. The problem was solved by making some changes in the selection process and after conducting courtyard meetings with the community volunteers, religious leaders, school teachers, and other influential community members. Conclusion: At the beginning of implementation, SoLiD was challenging, but project staff, along with the support of community volunteers and leaders, found Anchal to be a unique approach for the prevention of child drowning. Learning Outcomes: With the help of community volunteers, leaders, and project staff, child drowning prevention could be possible in similar LMIC settings.